2019
DOI: 10.4102/phcfm.v11i1.2000
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body composition and blood pressure among primary school children in Eastern Cape province, South Africa

Abstract: BackgroundIn South Africa, especially in the Eastern Cape province, despite reported high prevalence of underweight and obesity, little is known regarding the relationship of body composition (BC) with blood pressure (BP) in primary school children. Understanding the relationship between BC and BP in these children is important because it is associated with adverse effects on health and social repercussion in both adolescence and adulthood.AimThe aim of this study was to examine the relationship between BC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
6
17
0
Order By: Relevance
“…A study by Mushengezi and Chillo [18] found similar results, but also including significant correlation with fat mass. Another study by Gomwe et al [2] also showed numerous anthropometric variables that were significantly correlated with SBP in children, including stature, weight, BMI, WC, triceps, subscapular, gluteal skinfold thicknesses and percentage body fat, excluding WHR. A study by Gaskin et al [19] reported that there was an association between constantly increased blood pressure and increased body size and gender-specific body composition characteristics among adolescents.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…A study by Mushengezi and Chillo [18] found similar results, but also including significant correlation with fat mass. Another study by Gomwe et al [2] also showed numerous anthropometric variables that were significantly correlated with SBP in children, including stature, weight, BMI, WC, triceps, subscapular, gluteal skinfold thicknesses and percentage body fat, excluding WHR. A study by Gaskin et al [19] reported that there was an association between constantly increased blood pressure and increased body size and gender-specific body composition characteristics among adolescents.…”
Section: Discussionmentioning
confidence: 88%
“…Using an electronic Micronta monitoring kit, at least three readings of systolic blood pressure (SBP) and diastolic pressure (DBP) were taken at an interval of five minutes apart after the participants had been seated for 5 minutes or longer [17], the average from the three BP readings were calculated. Blood pressure measurements were categorised according to SBP and/or DBP percentiles as follows: normal BP-average SBP and/or average DBP <90th percentile; prehypertension-average SBP and/or average DBP ≥90th percentile but <95th percentile; and hypertension-average SBP and/or average DBP ≥95th percentile [2].…”
Section: Blood Pressurementioning
confidence: 99%
See 3 more Smart Citations